2019
DOI: 10.1002/jia2.25273
|View full text |Cite
|
Sign up to set email alerts
|

Access to sexual and reproductive health services for women living with HIV in Latin America and the Caribbean: systematic review of the literature

Abstract: Introduction Systematic reviews show that women living with HIV ( WLHIV ) have high unmet sexual and reproductive health ( SRH ) needs due to barriers to access sexual and reproductive health services ( SRHS ). In Latin America and the Caribbean ( LAC ), as of 2016, there were nearly one million WLHIV , but the existing evidence of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…For women, the specific socio-demographic characteristics which, together with healthcare decision making capacity, influence HIV testing include age, education, wealth, employment, residence, and parity [ 8 , 15 ]. In SSA, literature on women’s decision-making capacity and HIV testing is limited to specific countries such as Tanzania [ 8 ], Ethiopia [ 16 ], and South Africa [ 17 ] and mostly among women who are accessing healthcare services at health facilities [ 18 , 19 ]. This suggests the paucity of studies on women’s decision-making and HIV testing in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…For women, the specific socio-demographic characteristics which, together with healthcare decision making capacity, influence HIV testing include age, education, wealth, employment, residence, and parity [ 8 , 15 ]. In SSA, literature on women’s decision-making capacity and HIV testing is limited to specific countries such as Tanzania [ 8 ], Ethiopia [ 16 ], and South Africa [ 17 ] and mostly among women who are accessing healthcare services at health facilities [ 18 , 19 ]. This suggests the paucity of studies on women’s decision-making and HIV testing in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…Specific women's characteristics such as age, education, wealth, employment, residence, parity, participation in household decision-making and justification for sexual violence have been found to influence HIV testing [8,12]. In SSA, literature on women decision-making capacity and HIV testing are limited to specific countries such as Tanzania [8], Ethiopia [13] and South Africa [14] and mostly among women who are accessing health care services at health facilities [15,16]. This suggests the paucity of studies on women's decision-making and HIV testing in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of studies with WLHA in Latin America revealed higher prevalence of unmet contraceptive needs, unplanned pregnancies, induced abortions, risk of sterilization in the immediate postpartum, and exposure to sexual and institutional violence in WLHA compared to WNLHA. The reduction in institutional barriers, facilitation of access to services, and reduction of stigma and discrimination by health professionals are necessary in order for WLHA to make their sexual and reproductive choices free of violence and coercion 32 .…”
Section: Women's Characteristicsmentioning
confidence: 99%